2001
DOI: 10.1080/01690960143000056
|View full text |Cite
|
Sign up to set email alerts
|

The source of a lexical bias in the Verbal Transformation Effect

Abstract: Comparisons of responses to words and pseudowords gure prominently in our efforts to understand how spoken words are recognised. This was apparent in many of the presentations at the SWAP meeting (e.g., Fowler & Brancazio, 2000;Frauenfelder & Content, 2000). Differences in responding to words and pseudowords are assumed to demonstrate the in uence of lexical memory in the task at hand, from which we infer the structural and functional characteristics of the processing system.Each task we use in this enterprise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 8 publications
0
8
0
Order By: Relevance
“…In a series of works with the VTE, Pitt and colleagues contributed to better specify the VTE methodology, exploiting such ingredients as the number of displayed forms, the time spent on each form, the frequency of switches, etc (Pitt & Shoaf, 2001. They displayed three series of mechanisms at work in the VTE.…”
Section: Iii2 Auditory Phonetic and Lexical Mechanisms In The Vtementioning
confidence: 99%
“…In a series of works with the VTE, Pitt and colleagues contributed to better specify the VTE methodology, exploiting such ingredients as the number of displayed forms, the time spent on each form, the frequency of switches, etc (Pitt & Shoaf, 2001. They displayed three series of mechanisms at work in the VTE.…”
Section: Iii2 Auditory Phonetic and Lexical Mechanisms In The Vtementioning
confidence: 99%
“…This transformation process persists throughout the repetition procedure, leading to perceptual transitions from one speech form to another. Although verbal transformations have mainly been studied as a purely acoustical/auditory effect (e.g., MacKay, Wulf, Yin, & Abrams, 1993;Pitt & Shoaf, 2001Warren, 1961), it has been shown that the effect occurs not only during a purely auditory procedure but also during an overt or covert repetition procedure (Reisberg, Smith, Baxter, & Sonenshine, 1989;Sato, Schwartz, Abry, Cathiard, & Loevenbruck, 2006;Smith, Reisberg, & Wilson, 1995).…”
Section: Methodsmentioning
confidence: 99%
“…It has been shown that the number of transformations heard by listeners depends on stimulus length, interstimulus interval, and listening duration (Warren, 1961). Previous studies have reported that perceptual changes to auditory input could range from small phonetic deviations to strong semantic distortions, including substitution of a phoneme by a phonetically close one (Warren, 1961;Warren & Meyers, 1987), auditory streaming/perceptual grouping (Pitt & Shoaf, 2001, and lexical and semantic transformations (Kaminska et al, 2000;Warren, 1961). Lexical and sublexical levels of representation have been suggested as the loci of such effects.…”
Section: Verbal Transformations: a Window Into Speech Representationsmentioning
confidence: 99%
“…The classic paradigm consists in presenting participants with an auditory speech stimulus looped on a tape (see, e.g., Kaminska, Pool, & Mayer, 2000;Pitt & Shoaf, 2001Warren, 1961Warren, , 1982Warren & Meyers, 1987). It has been shown that the number of transformations heard by listeners depends on stimulus length, interstimulus interval, and listening duration (Warren, 1961).…”
Section: Verbal Transformations: a Window Into Speech Representationsmentioning
confidence: 99%